Rewriting Widowhood: Disrupting Patriarchal Family Ideas Through Digital Feminist Narratives - Shakira Yunas; Jordy Satria Widodo; Dyah Kristyowati (Ma Chung Press, 2026)
Abstract. Widows in Indonesian society often face social stigma shaped by patriarchal norms and traditional expectations of women’s roles within the family. They are frequently associated with negative stereotypes that portray them as immoral, socially disruptive, dependent, or incompatible with dominant family ideals. While previous studies have explored widowhood stigma through interviews, field observations, and media analysis, limited research has examined how stigma and resistance are constructed through organizational digital discourse. This study analyzes how narratives of widowhood are represented and challenged through Instagram captions published by @yayasanpekka between 2018 and 2025. The captions were compiled into a textual corpus and analyzed using AntConc to identify dominant keywords and recurring narrative patterns. Corpus-assisted analysis was combined with qualitative interpretation and Sandra Harding’s Standpoint Theory to examine how widows’ lived experiences are articulated as feminist knowledge. The findings show that keywords such as perempuan (women), desa (village), mereka (they), keluarga (family), and kelompok (group) reflect women’s agency, rural community, family responsibility, and collective solidarity. The analysis further reveals that @yayasanpekka reconstructs widowhood from a stigmatized marital status into an active social identity by representing widows as dignified women, family leaders, knowledge producers, and members of a collective social movement. The study concludes that Yayasan PEKKA’s Instagram account functions not only as an informational platform, but also as a digital feminist space that resists misogynistic representations and reshapes public perceptions of widowhood in Indonesian society. Keywords: widowhood, social stigma, digital feminist discourse, digital humanities, @yayasanpekka